Strategic Choices of Online Retailers in Live-Streaming E-Commerce - Jiang, Tao; Sun, Yuying; Guo, Youwei (International Journal of Industrial Engineering: Theory, Applications and Practice, 2025)
Some online retailers, based on traditional channels, have launched live-streaming channels. To study the optimal live-streaming choices of online retailers, this paper models the supply chain composed of a manufacturer and an online retailer by establishing three modes: no live-streaming mode, influencer live-streaming mode, and retailer self-live-streaming mode. The online retailer's optimal choice of live-streaming mode is derived by analyzing the equilibrium solutions. The results suggest that when the sales ability of the employee-streamer and the live-streaming consumer purchase rate are high, it's always advantageous to opt for retailer self-live-streaming mode. Affected by the influencer's commission rate and fixed participation fee, the influencer live-streaming mode is harmful to the online retailer. However, if the influencer chooses a profit-sharing mechanism, the online retailer and influencer can achieve a Pareto profit improvement, and online retailers will open the influencer live-streaming mode.